Do the different life history strategies of ants and honeybees determine fat body morphology?. (July 2022) - Wójcik, Łukasz; Chęć, Magdalena; Skowronek, Patrycja; Grabowski, Marcin; Persona, Kamil; Strachecka, Aneta
Abstract: The separation of two sister groups such as ants and bees in the Cretaceous involved the development of distinctive characteristics to occupy separate ecological niches. From the point of view of biology and ecology, it is important to see how different life history strategies affect the physiology of these insects. The fat body is the most metabolically important tissue in the organism of each insect. Therefore, we conducted a comparative analysis of the morphological image of the subcuticular fat body in different localisation/segments in Formica ( Seviformica ) cinerea and Apis mellifera mellifera foragers, because of the similarity of their functions in colonies. We observed that the fat bodies of ants and bees were composed of the same cell types: trophocytes and oenocytes. However, in each of the segments, the fat body cells in ants were bigger and there were fewer of them in comparison with bees. The dorsal part of the fat body of ants had a bilayer structure, where the outer layer was formed by binucleated oenocytes. Binucleated oenocytes were also found in the inner layer near the heart and tracheole. In bees, the fat body was unilayered and the trophocytes and oenocytes were present side by side. The similarities and, in particular, the differences in the structure of the fat body are the adaptation of these sister groups to life in a diverse environment. Highlights: The structure of the fat body of foragers of honey bees and ants was compared. The fat body of honeybees is segmental. The fat body of Formica ( Seviformica ) cinerea is layered. Environmental influence as one of the main determinants of fat body structure and physiology.